Association of gut microbiota with COVID‐19 susceptibility and severity: A two‐sample Mendelian randomization study. Issue 4 (20th April 2023) - Shang, Weifeng; Zhang, Sheng; Qian, Hang; Pan, Xiaojun; Huang, Sisi; Wen, Zhenliang; Liu, Jiao; Chen, Dechang
Abstract: Evidence supports the observational associations of gut microbiota with the risk of COVID‐19; however, it is unclear whether these associations reflect a causal relationship. This study investigated the association of gut microbiota with COVID‐19 susceptibility and severity. Data were obtained from a large‐scale gut microbiota data set ( n  = 18 340) and the COVID‐19 Host Genetics Initiative ( n  = 2 942 817). Causal effects were estimated with inverse variance weighted (IVW), MR‐Egger, and weighted median, and sensitivity analyses were implemented with Cochran's Q test, MR‐Egger intercept test, MR‐PRESSO, leave‐one‐out analysis, and funnel plots. For COVID‐19 susceptibility, IVW estimates suggested that Gammaproteobacteria (odds ratio [OR] = 0.94, 95% confidence interval [CI], 0.89–0.99, p  = 0.0295] and Streptococcaceae (OR = 0.95, 95% CI, 0.92–1.00, p  = 0.0287) had a reduced risk, while Negativicutes (OR = 1.05, 95% CI, 1.01–1.10, p  = 0.0302), Selenomonadales (OR = 1.05, 95% CI, 1.01–1.10, p  = 0.0302), Bacteroides (OR = 1.06, 95% CI, 1.01–1.12, p  = 0.0283), and Bacteroidaceae (OR = 1.06, 95% CI, 1.01–1.12, p  = 0.0283) were associated with an increased risk (all p  < 0.05, nominally significant). For COVID‐19 severity, Subdoligranulum (OR = 0.80, 95% CI, 0.69–0.92, p  = 0.0018), Cyanobacteria (OR = 0.85, 95% CI, 0.76–0.96, p  = 0.0062), Lactobacillales (OR = 0.87, 95% CI, 0.76–0.98, p  = 0.0260), Christensenellaceae (OR = 0.87, 95% CI, 0.77–0.99, p  = 0.0384), Tyzzerella3 (OR = 0.89, 95% CI, 0.81–0.97, p  = 0.0070), and RuminococcaceaeUCG011 (OR = 0.91, 95% CI, 0.83–0.99, p  = 0.0247) exhibited negative correlations, while RikenellaceaeRC9 (OR = 1.09, 95% CI, 1.01–1.17, p  = 0.0277), LachnospiraceaeUCG008 (OR = 1.12, 95% CI, 1.00–1.26, p  = 0.0432), and MollicutesRF9 (OR = 1.14, 95% CI, 1.01–1.29, p  = 0.0354) exhibited positive correlations (all p  < 0.05, nominally significant). Sensitivity analyses validated the robustness of the above associations. These findings suggest that gut microbiota might influence the susceptibility and severity of COVID‐19 in a causal way, thus providing novel insights into the gut microbiota‐mediated development mechanism of COVID‐19.